PARADIGMA PENDIDIKAN KRITIS DALAM PERSPEKTIF PENDIDIKAN ISLAM - Mohamad Adnan (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2015)
This study is an examination of the concept of critical education that is reviewed in a paradigmatic framework and see it in the perspective of Islamic education. Based on this, the fundamental issues of the study include the relevance, elaboration, and application in Islamic education. Therefore, this study is then expected to synthesize a more comprehensive educational paradigm and have scientific / theoretical and practical contributions to the development of the concept of Islamic education. Methodologically, this research is a study of qualitative analysis (literature) by maximizing philosophical, normative, pedagogical and interdisciplinary approaches to be developed in looking at how the concept of critical education and its actualization in Islamic education. Education aims to work on the human reality that has consciousness, free will, critical reason, and creativity. Therefore, methodologically critical education must rest on the principles of action and total reflection. That is the principle of acting to turn a static reality into a dynamic state for individual educators (educators and learners) as well as society as a whole. Based on the critical education paradigm, then education is expected to generate critical reasoning, creative ability, freedom in appreciation, and critical awareness of learners. Therefore, the pedagogic pattern that becomes the main patron used in the teaching and learning process in the education system so far has to be replaced by the pattern of andragogical education which is more open to the learner to actively participate, critically and creatively in teaching and learning process. Referring to the concept of Islamic education, basically Islamic education emphasizes humanization and liberation as an education orientation, and puts learners and educators alike as subjects in the learning process. Therefore, the Islamic educational paradigm base all the ideas, goals, and educational process on the foundation of spirituality and a solid faith to God and His Messenger. Or in other words, Islamic education combines aspects of vertical (spirituality) and horizontal (social) as the orientation of education. This is in contrast to the paradigm of critical education which emphasizes only the orientation of its education on material matters, and does not pay much attention to the aspect of spirituality which is the most sublime side in man